(untitled) (The Macau Ricci Institute Journal, 2023)
In the philosophical context, the term “holiness” can refer to spiritual excellence or wholeness. In classical Confucianism, “holiness” could be expressed using the virtue of cheng since it contains the meaning of integrity or wholeness. The process of spiritual transformation unfolds over three stages according to a traditional Christian understanding. Beginners go through the purgative stage, the proficient undergo the illuminative stage while the perfect pass through the unitive stage. Similarly, spiritual transformation is described in three stages in the Daxue (The Great Learning ). Beginners manifest the brightness of virtue in themselves, the proficient restore the brightness of virtue in others and the perfect attain utmost goodness. The Daxue also presents a detailed outline of eight steps required for spiritual transformation, namely, investigation of things, perfection of knowledge, formation of holy intentions, rectification of the mind, cultivation of the self, regulation of the household, good governance of the state and attainment of world peace. On this account, the purgative stage requires the first five steps while the illuminative stage requires the last three steps. The unitive stage involves a profound repetition of the entire eight steps.